The Effect of Barium Substitution on the Ferroelectric Properties of Sr2Nb2O7 Ceramics. Issue 4 (24th December 2012) - Gao, Zhipeng; Ning, Huanpo; Chen, Chen; Wilson, Rory; Shi, Baogui; Ye, Haitao; Yan, Haixue; Reece, Michael J.; Jones, J. L.
<x xml:space="preserve">Abstract</x> This work revealed that the solid solution compounds of Sr2−xBaxNb2O7 are promising lead‐free materials for high‐temperature piezoelectric sensor application. These compounds were confirmed as ferroelectric materials with high Curie points (> 900°C) by their piezoelectric activity after poling, ferroelectric domain switching in their P–E hysteresis loops and thermal depoling behavior. The effect of Ba substitution on the structure and properties of Sr2−xBaxNb2O7 (x < 1.0) was investigated. The solid solution limit of Sr2−xBaxNb2O7 was determined by XRD as x < 0.6. The a‐, b‐, c‐ axes, and cell volume increase with Ba addition. The textured ceramics of Sr2−xBaxNb2O7 were prepared for the first time. The highest d33 was measured as 3.6 ± 0.1 pC/N for Sr1.8Ba0.2Nb2O7.